China's Dual Identity and Its Discourse Toward the EU's Carbon Border Adjustment Mechanism - Joshua Kharizetha Evangelize Syauta (Master's Programs in International Relations, Faculty of Social and Political Science, Jenderal Achmad Yani University (UNJANI)., 2025)
The European Union’s Carbon Border Adjustment Mechanism (CBAM) affects China’s export interests and provides a stage for identity performance in policy discourse. This article examines how China’s dual identity as a developing country and as a responsible major power structures its assessment of CBAM and its implied responses. Using qualitative content analysis with a MIC-mini coding scheme, the study analyzes 41 elite and semi-mass texts and translates four variables (Self, Other, Valence, Action) into comparable indicators, including the Identity Salience Index (ISI), Average Valence Score (AVS), and Action Orientation (AOR) under a 60 percent dominance rule. Findings show a stronger responsible major power framing in 2023, a persistently negative tone that becomes more legal and procedural, and action signals that shift from protest toward technical coordination. Developing country references persist, preserving flexibility between equity claims and rule-shaping. The study offers a replicable way to quantify identity in discourse and to link identity emphasis to tone and implied action.